2010
DOI: 10.1111/j.1537-2995.2010.02582.x
|View full text |Cite
|
Sign up to set email alerts
|

Supernates from stored red blood cells inhibit platelet aggregation

Abstract: Substances that decrease expression of GPIIb/IIIa and inhibit PLT aggregation accumulate in NLR RBCs. Accumulation of this material is prevented by leukoreduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…By studying reconstituted whole blood instead of unmixed platelet concentrates, the interaction with RBCs and plasma, resembling the clinical situation of a transfused patient more closely, is also taken into account in our study. Multiple in vitro and in vivo studies have indicated that RBCs and plasma affect platelet function and haemostasis . When stored platelets are ex vivo mixed with whole blood, the agonist‐induced CD62P expression and aggregation improve , which implies the influence of RBCs and/or plasma on platelet function.…”
Section: Discussionmentioning
confidence: 99%
“…By studying reconstituted whole blood instead of unmixed platelet concentrates, the interaction with RBCs and plasma, resembling the clinical situation of a transfused patient more closely, is also taken into account in our study. Multiple in vitro and in vivo studies have indicated that RBCs and plasma affect platelet function and haemostasis . When stored platelets are ex vivo mixed with whole blood, the agonist‐induced CD62P expression and aggregation improve , which implies the influence of RBCs and/or plasma on platelet function.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence suggests that RBC transfusions modify hemostasis and thrombosis, supported by their association with substantial increases in both venous and arterial thrombosis in epidemiologic studies 9 . Therefore, it is likely that stored RBCs and supernatant mediators alter recipient PLT function 56 . Indeed, an in vitro transfusion model demonstrated that RBC transfusions affect PLT function in healthy adults 57 .…”
Section: Pltsmentioning
confidence: 99%
“…An in vitro study suggested that the platelets in fresh WB were more reactive with collagen and may therefore be more able to adhere at the site of injury and participate in primary platelet plug formation than those stored for extended periods . Additionally, stored supernatants of red cells have been shown to inhibit platelet aggregation .…”
Section: Introductionmentioning
confidence: 99%